Form and Meanings of Traditional Foods in Tanjung Village Commmunity Mempawah West Kalimantan - aditya, farninda (The Pontianak State Institute of Islamic Studies, 2018)
Traditional culinary is a legacy of regional wealth. From its creation it is taught from generation to generation. From the mention of its name, the name traditional food is a local language that preserves traditional languages. Traditional culinary is also closely related to tradition and special day. Traditional food has certain functions and meanings from that special day. The village of Tanjung Mempawah is a Coastal Village in Mempawah Hilir District. This village has a variety of traditional foods that are still entrenched. These foods are also served on certain days. The language used by the people of Tanjung Village is Malay. This study discusses the Forms and Meanings of Traditional Foods in Kampung Tanjung Mempawah Community